Characterization of the complete chloroplast genome of Dalbergia cultrata (Leguminosae) - Liu, Yu (Mitochondrial DNA B Resour, 2019)
Dalbergia cultrata is a Near Threatened species with high ecological and economic values. In this study, its chloroplast genome was assembled using Illumina pair-end sequencing dataset. The chloroplast genome has a quadripartite structure with 156,385 bp in length and contains a pair of 16,392 bp inverted repeat (IR) regions, which were separated by large single copy (LSC: 86,040 bp) region and small single copy (SSC: 37,561 bp) region. A total of 121 genes were annotated, including 77 protein-coding genes (PCGs), 36 tRNAs, and 8 rRNAs. The overall GC content was 36.1%. The phylogenetic analysis revealed that D. cultrata has close relationship to D. hainanensis and D. odorifera. This complete chloroplast genome can be readily used for population genetic studies of D. cultrata.